The Policy Of The Death Penalty For Perpetrators Of Corruption Is Studied From A Sociological Perspective Of Law - Munasto, Daud (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2022)
Corruption as an extraordinary crime provides regulations regarding the death penalty for the perpetrators. However, the fact is that this provision has never been applied by judges in adjudicating corruption cases. Therefore, corruption continues to occur and has expanded both the mode and the perpetrators. The formulation of Article 2 paragraph (2) UUTPK relating to "emergency conditions" is difficult to fulfill its elements. The formulation of the word "can be sentenced to death", provides an opportunity for judges to impose other heaviest criminal alternatives that are not in the form of a crime of loss of life opportunity, namely imprisonment for a certain period of time; or a maximum of 20 years or life imprisonment. The purpose of this study is to determine and explain the quality of the policy formulation of capital punishment for criminals. The research method used is normative juridical, the research specification is descriptive analysis, data collection techniques through library research. The results of this study are first, a review of the sociology of capital punishment for perpetrators of criminal acts of corruption. Efforts to tackle corruption must be carried out thoroughly both for law enforcers of corruption crimes and must be completely free from the intervention of any party with a legal sociology approach. Keywords: Corruption Crime; Death Penalty Sanctions; Legal Sociology Perspective.